PS 18-07 HEALTH LITERACY AND ITS ASSOCIATION WITH KNOWLEDGE OF HYPERTENSION IN EASTERN NEPAL. (September 2016) - Shrestha, Abha; Singh, Suman Bahadur; Maskey, Robin; Khanal, Vijay Kumar; Bhattarai, Sailesh; Pokharel, Paras Kumar
Abstract : Objective: The objective of this study was to find out the level of health literacy and its association with knowledge of hypertension among hypertensive patients in Eastern Nepal. Design and Method: We conveniently recruited 164 hypertensive patients (30–79 years) diagnosed with hypertension for at least a year from primary or tertiary care clinics in eastern Nepal. Health literacy was measured using a validated European Health Literacy Survey-Asia (HLS-EU-Asia) questionnaire. We translated the questionnaire into Nepali language and validated linguistically by back translation. The questionnaire measured health literacy in four domains of health information: assessing (4 questions), understanding (6 questions), appraising (3 questions), and applying (3 questions) in a likert scale of very difficult (=1) to very easy (=4). We categorized the total score as Inadequate health literacy (score 0–8), Problematic health literacy (score 9–12) and sufficient health literacy (score 13–16). Hypertension knowledge was measured using a validated questionnaire with 25 questions with total possible scores of 25, higher score indicating higher knowledge. Multiple regression analysis was done to predict the aspect of knowledge of hypertension. Results: The health literacy was inadequate among 51.8% of the participants; problematic among 22% and sufficient among 26.2%. Respondents with inadequate health literacy knew less about hypertension (12.38 ± 5.230) compared to sufficient heath literacy (18.70 ± 4.296) p < 0.001. Health Literacy was the strongest predictor of knowledge regarding hypertension (β = 0.16; 95% CI = 0.06–0.25) on multiple regression analysis after adjusting for age, gender, higher education, being married, family history of disease, regular visit to the clinic, information received regarding disease at clinic, smoking habit, and alcohol intake. Conclusions: The prevalence of limited health literacy was very high (73.8%) among hypertensive patients in our study and sufficient health literacy was associated with better knowledge of hypertension. Therefore, improving health literacy of these patients will bring better outcomes.